Saving Afghanistan - Krishnappa, V.; D'Souza, Shanthie Mariet; Singh, Priyanka (Academic Foundation in association with Institute for Defence Studies and Analyses, 2009)
Contributed articles presented at the conference at the Institute for Defence Studies and Analyses in February 2008.